The Qur'an and Hadith as a Rule of Law Change: Fatwa Studies of Islamic Organizations in West Java - Khaeruman, Badri; Nurholis, Nurholis (UIN Sunan Gunung Djati Bandung, 2024)
This study examines how Islamic organizations in West Java use the Qur'an and Hadith as foundations for legal rulings (fatwas) in response to modern challenges. Focusing on Muhammadiyah, Nahdlatul Ulama (NU), and Persatuan Islam (Persis), the research highlights how ijtihad (Islamic legal reasoning) adapts to social and technological changes. Comparative analysis reveals distinct methodological approaches: Muhammadiyah employs rational-textual methods (bayani, qiyasi, istishlahi), NU combines traditionalism with contextual flexibility, while Persis strictly follows scriptural sources. These differences produce varying fatwas - for example, Muhammadiyah declares smoking haram (forbidden) due to health risks, whereas NU and Persis consider it makruh (discouraged) due to weaker scriptural evidence. These variations stem from differing interpretations of texts, social considerations, and methodological priorities. The findings demonstrate Islamic law's ability to address contemporary issues while maintaining core principles. The study suggests that fatwa differences reflect each organization's intellectual tradition and social context rather than fundamental disagreements about Islamic law. Future research could explore: (1) regional variations in fatwa formulation across Indonesia, (2) interdisciplinary studies combining Islamic jurisprudence with social sciences, and (3) the impact of digital technology on ijtihad processes. Such studies would deepen understanding of how Islamic legal traditions interact with modernity in diverse Muslim communities.